The US Caselaw as a living system. - Carlos G O Fernandes; Erneson A Oliveira; Rilder S Pires; João A Monteiro Neto; J Ernesto Pimentel Fh; José S Andrade; Vasco Furtado (PLoS ONE)
This study presents an innovative exploration of the American Caselaw database, encompassing more than five million legal cases spanning three centuries of American history. Using complex network analysis, we reveal the organic nature of the US Caselaw, fundamentally anchored in common law. Through analysis of citation and bibliographic coupling networks, we shed light on the system's internal structure, unveiling communities delineated by regional, federal jurisdiction, and clustering based on similar legal citations. Our research uncovers a remarkable allometric relationship between the activity of judges and the legal case citations, reflecting the analogy between metabolic rate and body mass correlation observed in biological organisms. Furthermore, our results show a consistent self-similar characteristics of the communities and their maximum spanning trees, which also provides relevant insight into the origin of the allometric behavior. This analysis not only reveals the US Caselaw as a "living" entity but also sets a precedent in Caselaw-based judicial system studies, reinforcing the notion of its dynamic, organic functionality in the realm of analyzing complex legal systems.